When is a meet not a meet - Goldsmith, W.; Richards, R. (1999)
On how with a little thought and planning, swim meets provide opportunities to fine tune swimming performance that training alone cannot. On the following cases: - Swim meets for the coach - Swim meets for the swimmer There are many different ways of approaching a meet, each designed to develop a specific racing or competition skill : 1. The "only swim one event" meet. 2. The "do everything on the program" meet. 3. The "do a P.B. in the heats" meet. 4. The "do a P.B. in the finals" meet. 5. The "lane" meet. 6. The "swim long" meet. 7. The "everything goes wrong" meet. 8. The "negative" meet. 9. The "win everything" meet. 10. The "challenge" meet. Competition is the best form of training. Every competition should be used as an opportunity and as a learning experience designed to help you achieve your goals.